UTILIZATION OF SOCIAL MEDIA ON REPRODUCTIVE HEALTH KNOWLEDGE AMONG ADOLESCENTS - Heriza Syam; Jehanara; Janeta Lucky Safitri; Fauziah Yulfitria (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
Social media is currently very popular and is routinely used by teenagers. There are 98% of children and adolescents who know about the internet and 79.5% of them are internet users. Adolescents need to understand information about their reproductive health properly and correctly. With the existence of technology and high utilization of social media, teenagers should be able to access reproductive health information easily. It was a descriptive quantitative study using a cross sectional study design. The population was all students of a high school with a study sample of 100 respondents and the sample technique was stratified random sampling. As many (91%) respondents used social media to find information about reproductive health. More (94%) male respondents used social media to increase knowledge of reproductive health than female respondents who only 88%. Most respondents had sufficient knowledge, namely (40%). The type of social media that was often used by students was the website (36%). The majority of the respondents therefore had sufficient knowledge about reproductive health by utilizing social media as a source of information.